HUBUNGAN DUKUNGAN SUAMI SAAT ANTENATAL DAN INTRANATAL DENGAN BOUNDING ATTACHMENT PADA IBU POST PARTUM DI RSU PANCARAN KASIH GMIM MANADO (JURNAL KEPERAWATAN, 2015)
Abstrack: During pregnancy a wife needs a pair of support that comes from the husband. Husband to the mother's lack of support will lead to not nurture drope affection between mother and baby or not nurtured bounding attachment to mother and baby. The purpose of this study was to determine the relationship of husband support during antenatal and intranatal with bounding attachment on post partum mothers at General Hospital Pancaran Kasih GMIM Manado. The design of this research was descriptive analytic cross sectional design. Samples were taken through out the post partum mothers in pavilium Maria at General Hospital Pancaran Kasih GMIM Manado numbered 34 people with the sampling technique was total sampling. The results of this study was the relationship of support from husband during antenatal with the bounding attachment obtained significant P value = 0.001 mean P value